La información virtual de los medios de comunicación en el cantón Balzar, Provincia del Guayas, año 2020 - Campuzano Ochoa, Genesis Lisbeth (2021)
In recent decades, virtual information systems have undergone changes due to the development and dissemination of new information and communication technologies through the Internet. There are a hundred numbers of information resources that offer life to the Internet, and in addition to this there are numerous investigations that have been able to predict that with the passing of the years we will find ourselves immersed in the technology that will replace all the material things that we use daily to perform any type of activity. In addition to the aforementioned, if we project into the future, we could guarantee that the most viable way to have an adequate communication is through technology. It is for this reason that it is necessary to commit to adopt means of communication that contribute with an adequate virtual information. While it is true that people do not always use the information presented in the virtual media in an adequate way, since they usually present false news and users make criticisms, mockery regarding the subject or simply make ill-intentioned comments without realizing the damage or the consequences that they can bring. It is for this reason that this research was conducted in order to provide adequate information by the virtual method through the media for Balzar Canton, Guayas Province.